Dispersal and fire limit Arctic shrub expansion - Yanlan Liu; William J. Riley; Trevor F. Keenan; Zelalem A. Mekonnen; Jennifer A. Holm; Qing Zhu; Margaret S. Torn (Nature Communications, 2022)
Shrub encroachment trends are widespread yet complex. Here the authors demonstrate that not considering dispersal and fire leads to overestimating shrub expansion in Arctic tundra and therefore its role as carbon sink.